CEOs' early-life disaster experience and corporate earnings quality: Focusing on the Great Chinese Famine - Zhao, Yang; Hu, Jun; Liu, Lang (Frontiers in Psychology, 2022)
This paper aims to examine the impact of CEOs' early-life disaster experiences on corporate earnings quality. We proxy the disaster experience with whether CEOs lived through the Great Chinese Famine and the famine intensity they experienced. The results indicate that CEOs' early-life famine experience is significantly positively associated with corporate earnings quality, and the famine effects are more obvious for CEOs who experienced the famine at adolescent ages. Further tests show that the famine experience effects are more pronounced in companies with high investor protection and cross-listing and with CEOs who have a relatively high level of education or background in economic management. The findings suggest CEOs would bear the imprint of an adverse early-life experience, which has risk aversion and learning effects on their decision making in corporate earnings information disclosure.